A103 PIVOTING IN A PANDEMIC: THE IMPACT OF COVID-19 ON THE PROVISION OF CARE FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A PRELIMINARY ANALYSIS. (4th March 2021) - Malhi, G; Mikail, M; Minhas, G; Chambers, J; Khanna, R; Wilson, A
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak, also known as COVID-19, was declared a worldwide pandemic in March of 2020. Since the onset of the pandemic, the focus of many healthcare systems has shifted toward limiting non-essential visits to hospitals in order to prioritize and allocate resources toward treating those affected by COVID-19, and preventing further exposures. While the effect of COVID-19 has been felt amongst many patient populations, those with inflammatory bowel disease (IBD) have been particularly impacted through delayed appointments and endoscopy, which is critical in disease monitoring. Aims: We aimed to determine how changes to the provision of IBD care due to the COVID-19 pandemic have affected IBD patients. Methods: A retrospective cohort study was conducted using administrative data comparing IBD patients admitted to the gastroenterology ward from March 17 to August 31 2019, with IBD patients admitted from March 17 to August 31 2020 at a tertiary care centre in London, Ontario. Patients were reviewed to assess differences in care utilization and IBD-related outcomes such as hospitalization, surgery and length of stay and in-patient drug therapy. Results: A total of 538 patients (259 in 2019 cohort and 279 in 2020 cohort) were reviewed with 48 and 60 IBD patients meeting the inclusion criteria for 2019 and 2020 respectively. Patient demographics were similar between 2019 and 2020 cohort for age, sex, rurality, disease type, and biologic exposure. A greater proportion of patients were admitted with IBD flares in 2020 (86.7% vs 75%, p=0.03). Furthermore, the 2020 cohort also had a 45% increase in in-patient surgical consultations (p=0.07), a 50% increase in in-patient IBD-related surgeries (p=0.39), a 69% increase in inpatient Remicade prescription (p=0.13) and a 70% increase in infectious complications at presentation to hospital (p=0.21). A shorter median length of stay was reported for patients in the 2020 cohort (4 days IQR 3.95 vs 5.85 IQR 4.65, p=0.09). Conclusions: Preliminary data suggest that during the COVID-19 pandemic, we have seen more deleterious outcomes in our IBD patients such as increased flares necessitating hospital admission. There was also a non-significant trend toward increased infectious complications as well as in-patient surgeries and need for in-patient Remicade. Though these results cannot be fully interpreted due to the need for further sampling, they suggest that IBD patients may be at-risk for poor outcomes in the current climate of medical care. Completion of this study will help define the full impact of care shifts related to reducing the spread of the novel coronavirus on IBD patients and highlight areas of care that need careful assessment and consideration to protect IBD patient health. Funding Agencies: None